2018
DOI: 10.1186/s12913-018-3627-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economical impacts of guideline implementation by the pharmaceutical care unit for high cost medications in a referral teaching hospital

Abstract: BackgroundIrrational drug use is a global health challenge in all healthcare settings, such as hospitals. This study evaluated the impact of an intervention by the pharmaceutical care unit on the use pattern of high-value medications and their direct costs in a referral hospital.MethodsThis interventional, prospective study was carried out in clinical wards of Namazi Hospital (Shiraz University of Medical Sciences) during six months from May 2015 to October 2015. Clinical pharmacists completed the checklists f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
4
12
0
2
Order By: Relevance
“…The prominent study that specifically focused on this issue was performed by Mahmoudi et al in a teaching hospital in Shiraz, in which clinical pharmacists interventions were associated with considerable cost-saving [25]. Similar findings (55.88% that equals to 77,720 USD cost reduction per month) have been observed for albumin, intravenous pantoprazole, and intravenous immune globulin in another referral hospital in Shiraz [29].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The prominent study that specifically focused on this issue was performed by Mahmoudi et al in a teaching hospital in Shiraz, in which clinical pharmacists interventions were associated with considerable cost-saving [25]. Similar findings (55.88% that equals to 77,720 USD cost reduction per month) have been observed for albumin, intravenous pantoprazole, and intravenous immune globulin in another referral hospital in Shiraz [29].…”
Section: Discussionmentioning
confidence: 60%
“…The result showed that the total number of administered medications decreased significantly by 50.76% during the intervention period. Additionally, the direct cost of albumin and IVpantoprazole significantly decreased (55.8% and 83.92%, respectively) [29].…”
Section: Designing Protocols Improving Drug Utilization and Cost Samentioning
confidence: 96%
“…A Organização Mundial da Saúde sugeriu diferentes estratégias administrativas, educacionais e regulatórias para melhorar o padrão de uso de drogas, incluindo treinamento contínuo da equipe de saúde, diretrizes padrão de prática clínica e avaliação da utilização de drogas (8) . A implementação de diretrizes de prática clínica com base em um programa farmacêutico de contenção de custos aumenta a segurança do paciente através da minimização de efeitos adversos e interações medicamentosas, redução de Brazilian Journal of Development, Curitiba, v.7, n.4, p. 33453-33476 apr 2021 prescrições inadequadas de medicamentos, controle da resistência de patógenos bacterianos a agentes antimicrobianos, redução de custos, gerenciamento de suprimentos de medicamentos e melhoria da qualidade dos cuidados de saúde e promoção da satisfação do paciente (8,9) . Assim, este artigo possui como finalidade sintetizar evidências sobre intervenções farmacêuticas em pacientes oncológicos em uso de antibioticoterapia de uso restrito atendidos em Unidade de Terapia Intensiva quanto á redução da resistência bacteriana e promoção de economia financeira.…”
Section: Introductionunclassified
“…In Washington State, pharmacists need to sign health plans to provide post-diagnosis medication management [5]. Previous researches have proved that pharmacists can reduce PE [6][7][8]. Tareq et al [6] found that a clinical pharmacist's intervention in ICU totally saves $211,574.90 of drug therapy cost through a comparative study.…”
Section: Introductionmentioning
confidence: 99%
“…A randomised controlled trial has shown that pharmacists reviewing repeat prescriptions can reduce PE to £61 per elderly patient (≥65) per year [7]. Vazin et al [8] found that clinical pharmacists help decline PE by 50.76% by controlling the use of three high-cost medications, including albumin, intravenous (IV) pantoprazole and IV immune globulin. Some studies have demonstrated that dispensing pharmacists can reduce drug and package costs by managing drug storage, logistics and other medicine-handling procedures [9], while most studies have drawn the conclusion that clinical pharmacists participate in a patient's drug therapy, provide pharmaceutical care and reduce medication errors, which eventually cut down PE [10].…”
Section: Introductionmentioning
confidence: 99%